2018
DOI: 10.1021/acs.jpclett.8b02380
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Energy in Proteins Correlates with Topology

Abstract: The exchange of vibrational energy in proteins is crucial for their function. Here, we establish a connection between quantities related to it with geometry-based properties such as the proteins' residues coordination number. This relation is proven by molecular simulation in a neuropharmacologically relevant transmembrane receptor. The connection demonstrated here paves the way to studies of protein allostery and conformational changes based solely on protein structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…According to PCCA+, the two recognized clusters represents regions in which the E vib exchange processes among residues within the cluster is faster than the E vib exchange between the clusters themselves. This finding agrees with previously reported computational results showing that residues belonging to the regions identified by the clusters feature shorter characteristic time for E vib exchange 19 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…According to PCCA+, the two recognized clusters represents regions in which the E vib exchange processes among residues within the cluster is faster than the E vib exchange between the clusters themselves. This finding agrees with previously reported computational results showing that residues belonging to the regions identified by the clusters feature shorter characteristic time for E vib exchange 19 .…”
Section: Resultssupporting
confidence: 93%
“…and E vib but just their ratio p i (t)). L is the transition frequency matrix, whose elements L ij are the frequencies associated with transition times τ ij , which are the characteristic time to exchange E vib between residue i and j, as calculated in reference 19 . Each element of L is defined as:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of vibrational energy relaxation in proteins, ,,, part of a long-standing goal of describing relaxation dynamics in complex molecular environments, has led to a search for relatively simple models that capture its main features. This has included studies addressing the role of structure and bonding, dynamics, ,, and quantum mechanical effects. Coarse-grain modeling using a classical master equation offers a promising approach to model energy transport in proteins and protein complexes, ,, identifying regions along which transport is facile and reproducing energy dynamics quite well when compared with results of all-atom simulations. The master equation simulations support a diffusion-like picture for transport.…”
Section: Introductionmentioning
confidence: 99%
“…On length scales from about 2 Å to several nm, proteins exhibit properties of fractal objects, which provide a statistical description of energy transport and the emergence of networks of energy transport channels that span these molecules. The statistical similarity between the distribution of mass on the level of amino acids and at larger length scales of groups of amino acids has been associated with the subdiffusive energy dynamics observed in computational studies, vibrational dynamics of proteins, and the anisotropy of energy transfer observed in time-resolved vibrational spectroscopy. , Statistical properties of mass distribution indicate that energy transport is anisotropic and networks for long-range energy transport are ubiquitous in globular proteins. Networks of energy transport in proteins and between protein molecules, including long-range nonbonded networks in allosteric proteins that also include water molecules, , have been identified by computational studies , and probed by experiment. ,,, …”
Section: Introductionmentioning
confidence: 99%